PENGEMBANGAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR - Wildan Tamir Amanulloh; Supri Wahyudi Utomo; Farida Styaningrum (CATHA SAINTIFICA, 2025)
One of the main challenges in vocational education, particularly in accounting learning, is students’ low understanding of basic accounting concepts. This study aims to develop WordWall-based learning media integrated with the Self-Organized Learning Environment (SOLE) model and to examine its effectiveness in improving learning outcomes on Cooperative Accounting material at SMK Negeri 5 Madiun City. The research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, questionnaires, and pretest–posttest learning outcome assessments. The developed WordWall media was validated by material, language, and media experts and met the feasibility criteria for classroom use. The implementation involved 30 students of class XI Accounting. Questionnaire results showed a feasibility and practicality score of 85.21%, categorized as feasible for implementation. Learning outcomes demonstrated a substantial improvement, with the average pretest score of 64 and learning completeness of 6.67% increasing to an average posttest score of 88 with 96.67% completeness after the use of the media. These findings indicate that WordWall media integrated with the SOLE model effectively enhances students’ understanding and mastery of Cooperative Accounting concepts.  .